PENGARUH INTELLECTUAL CAPITAL, PERENCANAAN PAJAK DAN PENGUNGKAPAN ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN - Nisa Irwanda; Fitriyah (Jurnal Nusa Akuntansi, 2026)
This study aims to analyze the effect of Intellectual Capital, Tax Planning, and Enterprise Risk Management (ERM) disclosure on firm value in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. A quantitative approach is employed using panel data regression analysis. The independent variables include Intellectual Capital measured by the Value Added Intellectual Coefficient (VAIC™), Tax Planning measured by the Effective Tax Rate (ETR), and ERM Disclosure measured by a disclosure index. The dependent variable, firm value, is measured using the Tobin’s Q ratio. The study sample consists of 47 companies selected using purposive sampling, resulting in 235 firm-year observations over five years. The findings reveal that Intellectual Capital has a significant effect on firm value. Tax Planning does not have a significant impact, while ERM Disclosure has a positive and significant effect on firm value. Simultaneously, the three independent variables significantly influence firm value. These results highlight the importance of managing intellectual assets and increasing risk disclosure transparency to boost investor confidence and support the enhancement of firm value in the market.